Advantages of Using the Flipped Classroom Model in Science and Social Studies Instruction - Anđela N. Milovanović; Оlivera D. Cekić-Jovanović; Dušan P. Ristanović (University of Belgrade, Teacher Education Faculty, 2022)
In this research we explored the effects of using the flipped classroom model on the quality of students' knowledge about the issues related to the living nature. The applied model implied that the position and role of homework and schoolwork were switched and the multimedia resources were used to a great extent. The research was conducted using a quasi-experiment with parallel groups. The sample of teaching content comprised the segments of the teaching content for the school subject Science and Social Studies, while the sample of participants included 61 students of the third grade of elementary school (30 students respectively in control and experimental groups). In the experimental group, the selected content was taught using the flipped classroom model, whereas the frontal form of classroom interaction was used in the control group, with a minimal use of modern technology that was limited to Power Point presentations. Unlike the results of the initial test, which showed the uniformity of the groups in terms of the quality of the tested knowledge (reproduction, understanding, and practical application), on the final test of knowledge, the students of the experimental group demonstrated a significantly better achievement. They were more successful in solving tasks that required memorization of facts, critical reflection, solving problem situations, and practical application of knowledge in situations from everyday life. The conclusion of the research is that the application of the flipped classroom model in teaching the content of the Science and Social Studies has a positive effect on increasing the quality of students' acquired knowledge.